2007
DOI: 10.2134/jeq2006.0358
|View full text |Cite
|
Sign up to set email alerts
|

Depth Distribution of Sulfonamide Antibiotics in Pore Water of an Undisturbed Loamy Grassland Soil

Abstract: Despite the concern raised by the detections of veterinary antibiotics like sulfonamides (SA) in the environment, their fate in soils is still not sufficiently understood. In a previous article, we demonstrated that manure may substantially influence losses of SA via runoff from soils. Here, we report on the effect of manure on SA availability in soil pore water. Three sulfonamides (sulfadimidine, sulfadiazine, sulfathiazole) and two tracers (bromide and Brilliant Blue) were either applied in manure or as aque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
24
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 31 publications
3
24
1
Order By: Relevance
“…This is consistent with the determined transport of mobile fractions of sulfonamides into deeper soil layers in manure-fertilised soils in laboratory and field studies (e.g. Burkhardt and Stamm 2007;Hamscher et al 2005;Kay et al 2005a, b). Moreover, freshwater contamination was indicated by findings of sulfonamides in groundwater below and surface waters close to agricultural areas at concentrations ranging from 0.01 µg L −1 to 3.3 mg L −1 (e.g.…”
supporting
confidence: 88%
See 2 more Smart Citations
“…This is consistent with the determined transport of mobile fractions of sulfonamides into deeper soil layers in manure-fertilised soils in laboratory and field studies (e.g. Burkhardt and Stamm 2007;Hamscher et al 2005;Kay et al 2005a, b). Moreover, freshwater contamination was indicated by findings of sulfonamides in groundwater below and surface waters close to agricultural areas at concentrations ranging from 0.01 µg L −1 to 3.3 mg L −1 (e.g.…”
supporting
confidence: 88%
“…The highest losses in plot and lysimeter experiments were determined in loam, clayey and bedrock soil compared to sandy soils, which was attributed to preferential flow (e.g. Burkhardt and Stamm 2007;Höper et al 2007;Groeneweg et al 2007). Effects of precipitation were investigated by Blackwell et al (2009), who reported that the maximum leachate concentration of sulfachloropyridazine was increased from 0.66 to 8.5 µg L −1 after the rate of irrigation was increased by a factor of 2.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…A plausible explanation for not detecting SM in samples collected from the column at any depth could be a limitation of our analytical method, and/or is a result of inefficient extraction method to extract SM from the soil samples using DCM (Srinivasan et al, 2012). Burkhardt and Stamm (2007) reported the depth distribution of three sulfonamides applied to a loamy grassland soil; with levels of antibiotic concentrations at 30-50 cm depth being equal to the concentration found in the top 5 cm regardless of whether application of antibiotics was in manure or in aqueous solution. In the current study for both soils, the antibiotic concentration profile decreased with depth, indicating that possible preferential flow through cracks, or worm holes did not occur.…”
Section: Antibiotic Retardationmentioning
confidence: 99%
“…Some antibiotics can be biodegraded within a few days in soil (Burkhardt and Stamm 2007;Kotzerke et al 2008), while some other antibiotics can be persistent in soil with the half-life time of several months (Marengo et al 1997;Rosendahl et al 2012). The antibiotics, such as tetracyclines and quinolones (QNs), exhibit high adsorption properties to accumulate in soil on the surface of either mineral or organic soil constituents (Tolls 2001).…”
Section: Introductionmentioning
confidence: 99%